2002
DOI: 10.1007/bf03405035
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Hepatocellular Carcinoma in Canada

Abstract: Background and Methods: To provide information on poorly described Canadian hepatocellular cancer epidemiology, we analyzed incident cases abstracted from the Canadian Cancer Registration Database and Canadian annual death data . Age, sex, geographic distribution, and secular trends were described. Projection models were developed for the next decade.Results: Results indicated much higher incidence and mortality rates in males than females, with substantial increases for both with age. Age-standardized incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…The burden of illness associated with hepatocellular carcinoma (HCC) is an escalating public health problem worldwide . Studies using population‐based registries have shown an increase in HCC incidence and mortality in many countries over the past 30 years . In Canada, HCC incidence is expected to continue to increase over the next decade, with an average increase in the age‐adjusted incidence of 3.4% per year in men and 2.2% per year in women .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of illness associated with hepatocellular carcinoma (HCC) is an escalating public health problem worldwide . Studies using population‐based registries have shown an increase in HCC incidence and mortality in many countries over the past 30 years . In Canada, HCC incidence is expected to continue to increase over the next decade, with an average increase in the age‐adjusted incidence of 3.4% per year in men and 2.2% per year in women .…”
mentioning
confidence: 99%
“…Studies using population‐based registries have shown an increase in HCC incidence and mortality in many countries over the past 30 years . In Canada, HCC incidence is expected to continue to increase over the next decade, with an average increase in the age‐adjusted incidence of 3.4% per year in men and 2.2% per year in women . The increases in HCC incidence in some low‐risk areas, including Canada, suggest an underlying birth cohort effect linked to an increase in the incidence or prevalence of hepatitis C, immigration of people from countries with a high prevalence of hepatitis B and C, obesity, and diabetes mellitus .…”
mentioning
confidence: 99%
“…In general, more developed geographical regions such as North America, western Europe and Australia have a low HCC incidence relative to less developed geographical regions where hepatitis B viral infections (HBV) are endemic, such as sub‐Saharan Africa and southeast Asia (4). Yet, over the past few decades, the incidence of HCC has increased among some developed countries, including Canada (5–10).…”
mentioning
confidence: 99%
“…Chronic infection with Hepatitis B virus (HBV) and Hepatitis C virus (HCV) has been associated with the disease [2,3] with higher incidences reported in countries where Hepatitis B and or Hepatitis C are endemic [4,5] HCV has a lower global prevalence than HBV and is more often associated with HCC in economically developed regions [6,7]. Globally, HCC is increasingly becoming a major health concern with estimates of 500,000 new cases reported annually [8].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, HCC is increasingly becoming a major health concern with estimates of 500,000 new cases reported annually [8]. Some studies have shown a direct correlation between the geographical distribution of HBV and HCV and HCC prevalence [7]. In Japan and Italy where higher HCV prevalence is very high, HCC has been shown to be more prevalent [8].…”
Section: Introductionmentioning
confidence: 99%